METHODOLOGY OF USING THE CULTURAL ASPECT IN TEACHING THE UZBEK LANGUAGE AS A SECOND LANGUAGE IN THE GENERAL SECONDARY EDUCATION SYSTEM - Sobirova Mohlaroyim Adham qizi (Scholar Express Journal, 2023)
In the article, how to teach a second language, the stages of students’ acquisition of a second language, and the linguo-cultural approach in teaching Uzbek as a second language in the general secondary education system, or clearly defined tasks for teaching culture. The reasons for choosing the appropriate methodology and the six required teaching technologies are presented.
Keywords: linguacultural; second language; culture